Social Research about Online Crime: Key Global Paradigms and the State of Research in Lithuania - Šupa, Maryja (Information & Media, 2021)
This paper analyses key differences between two paradigms dominant in social research on online crime: the more prevalent neopositivist paradigm and the more recent critical–cultural paradigm. Based on an extensive analysis of up-to-date literature, the key paradigmatic oppositions in online crime research encompass: 1) in neopositivism, the conceptual separation of technological and social practices, the reliance on rational choice approaches in theory, especially routine activity theory, and the tendency towards quantitative research methods; 2) in the critical–cultural paradigm, a complex and context-dependent approach to the technosocial as a continuum, theoretical roots in critical theory, cultural criminology, actor-network theory, and feminist theory, and the emphasis on qualitative methods. The field of online crime research in Lithuania is dominated by legal studies, while social research is rare and fragmented. The existing social research of online crime in Lithuania lacks a solid theoretical basis in either paradigm. Methodologically, there are examples of both quantitative (surveys, analysis of registered crime statistics) and qualitative studies (interviews, discussion groups, content analysis). However, most of the studies are small-scale and their scarcity makes it nearly impossible to evaluate the strengths, weaknesses, and complimentary potential of each approach in the specific national and regional context.
Keywords: cybercrime; online crime; criminological theory; social research methodology; technology discourses; online research